2020
DOI: 10.1001/jamahealthforum.2020.0416
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Hospital-Acquired Condition Reduction Program Through Rulemaking

Abstract: Hospital-acquired conditions (HACs) are pervasive and expensive, and they cause unnecessary morbidity and mortality. As of 2017, 9 HACs still occurred for every 100 discharges. 1 The Hospital-Acquired Conditions Reduction Program (HACRP) was created to reduce this rate.Despite the critical need to improve safety, research indicates the HACRP has not been effective. While improvement on claims data-based measures accelerated after HACRP implementation, the program did not improve patient outcomes. 2 Risk adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Overall, the high cost and high mortality risk associated with HAC suggest that reducing HAC could improve health outcomes and save costs. However, current strategies to reduce HAC focused only on patient characteristics [ 7 ] or incident reporting scores [ 37 ], which has been criticised for not comparing the performance of hospitals with similar characteristics [ 38 , 39 ]. The benchmarking analysis in this study addresses this issue by comparing the safety performance of hospitals with similar characteristics using the data envelopment analysis framework.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the high cost and high mortality risk associated with HAC suggest that reducing HAC could improve health outcomes and save costs. However, current strategies to reduce HAC focused only on patient characteristics [ 7 ] or incident reporting scores [ 37 ], which has been criticised for not comparing the performance of hospitals with similar characteristics [ 38 , 39 ]. The benchmarking analysis in this study addresses this issue by comparing the safety performance of hospitals with similar characteristics using the data envelopment analysis framework.…”
Section: Discussionmentioning
confidence: 99%
“…Safety-net hospitals would still have strong incentive to reduce adverse events but would be more fairly judged against other facilities with a more similar case mix. Further, prior work 5,20,28,29 has found that the HACRP has not yet achieved its goal: the receipt of a penalty has not been associated with a change in the rate of hospitalacquired conditions or in patient outcomes. The HACRP as currently constructed could therefore inadvertently serve an in- After stratification, states that each received a total of less than $1 million in penalties compared with the prestratification scheme included California, Massachusetts, Michigan, and New York; states that each received a total of $1 million or more in penalties included Arkansas, Florida, Kansas, Kentucky, Mississippi, Ohio, Texas, and Virginia.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Given similar disparities in other CMS value-based payfor-performance programs, including the Hospital Readmissions Reduction Program (HRRP), 6,[15][16][17] many stakeholders have argued for the inclusion of social risk adjustment when evaluating hospital performance. 5,[18][19][20] In response, the US Congress passed the 21st Century Cures Act in 2016. This act mandates that hospitals in the HRRP be stratified into, and evaluated within, quintiles based on their "proportion dual," which is the proportion of their patients dually enrolled in Medicare and Medicaid.…”
mentioning
confidence: 99%
“…It is challenging to quantify the effect of the CMS hospital value-based programs because they have no control group, were initiated approximately concurrently, and depend on suboptimal measures and coding patterns to detect quality. For example, evaluations of the Hospital Acquired Condition Reduction Program have shown that the program was not associated with improved mortality rates and that its associations with improvements in patient safety are seen in claims-based measures but not in more reliable registry-based measures . Similarly, although early evidence suggested that enactment of the Hospital Readmissions Reduction Program (HRRP) was associated with reductions in readmissions, the observations were primarily driven by coding changes and statistical artifact .…”
mentioning
confidence: 99%
“…Perhaps most importantly, these value-based programs are regressive and have disproportionately penalized safety-net hospitals that serve poor and sick populations . Although CMS has saved billions of dollars through the imposition of penalties, the long-term effects of taking resources away from already resource-constrained hospitals may prove to have been penny-wise and pound-foolish.…”
mentioning
confidence: 99%